Researching creativity in second language acquisition - Pipes, Ashleigh (Second language acquisition research series, 2023)
Researching Creativity in Second Language Acquisition explains the links between creativity and second language learning and how to propel the research of creativity as an individual difference in second language acquisition forward at multiple levels. It features an array of sample research questions and methods for student and professional researchers, ranging from simple projects that can be executed from start to finish in 15 weeks all the way to multi-year project guidelines for more advanced scholars with additional time and resources. It also features in-class and out-of-class activity suggestions that will reinforce concepts in fun and creative ways. Using this book as a guide will save researchers time and effort in designing and executing their next projects as well as save instructors time in class planning. This book will be an invaluable resource to students and researchers of SLA, applied linguistics, TESOL, and psychology"--Provided by publisher.